Assessment in Mathematics Education Large-Scale Assessment and Classroom Assessment - Suurtamm, Christine; Thompson, Denisse R.; Kim, Rae Young; Moreno, Leonora Diaz; Sayac, Nathalie; Schukajlow, Stanislaw; Silver, Edward; Ufer, Stefan; Vos, Pauline (ICME-13 Topical Surveys, 2016)
This book provides an overview of current research on a variety of topics related to both large-scale and classroom assessment. First, the purposes, traditions and principles of assessment are considered, with particular attention to those common to all levels of assessment and those more connected with either classroom or large-scale assessment. Assessment design based on sound assessment principles is discussed, differentiating between large-scale and classroom assessment, but also examining how the design principles overlap. The focus then shifts to classroom assessment and provides specific examples of assessment strategies, before examining the impact of large-scale assessment on curriculum, policy, instruction, and classroom assessment. The book concludes by discussing the challenges that teachers currently face, as well as ways to support them. The book offers a common language for researchers in assessment, as well as a primer for those interested in understanding current work in the area of assessment. In summary, it provides the opportunity to discuss large-scale and classroom assessment by addressing the following main themes: ·Purposes, Traditions and Principles of Assessment ·Design of Assessment Tasks ·Classroom Assessment in Action ·Interactions of Large-Scale and Classroom Assessment ·Enhancing Sound Assessment Knowledge and Practices It also suggests areas for future research in assessment in mathematics education. .